Expectations and Saving Behavior: An Empirical Analysis - Stefan Arent (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2012)
In this paper we analyze the impact of the expectations about future labor income on thesaving behavior of German households. We measure expectations on an individual basisinstead of generalized risk measures as it is common in existing studies. We use aunique panel data set on household savings. We find that that a higher unemploymentexpectation significantly decreases savings. However, we are not able to identify asignificant relationship between general future income expectations and savings. Moreover,we find that good health expectations increase savings in Western Germany, butdecrease the savings in Eastern Germany.
Keywords: D12; D14; D31; D84; D91; 330; Income expectations; unemployment expectations; health expectations; saving behavior; savings; Sparen; Einkommen; Arbeitslosigkeit; Gesundheit; Erwartungstheorie; Schätzung; Deutschland